The Effect of Exercise Training as Adjuvant Treatment on Functional Capacity in Congenital Heart Disease with Negative Vaso Reactivity Test Pulmonary Hypertension Patient at Saiful Anwar Hospital Malang - Pratiwi, Irma Kamelia; Martini, Heny; Tjahjono, Cholid Tri; Anjarwani, Setyasih; Handari, Saskia Dyah (Heart Science Journal, 2023)
BackgroundPulmonary hypertension associated with congenital heart disease (CHD) is an important subgroup that accounts for approximately 11% of all patients with PAH. Physical limitations are one of the main symptoms of hemodynamic changes in patients with PH. Objective This study aimed to evaluate the effect of physical exercise therapy for 12 weeks as an additional therapy with PDE-5 inhibitors on the functional capacity of patients with Congenital Heart Disease accompanied by Pulmonary Artery Hypertension (CHD – PH). MethodThis research was an analytic experimental study with a prospective cohort research method. This study used data sources obtained from medical records to adjust subjects based on inclusion and exclusion criteria, initial cardiac training test examination data was carried out at IPJT in patients selected as subjects. The patient's clinical outcomes were followed in the next 12 weeks. ResultThis research was conducted on 16 samples divided into two groups, namely the control and study groups. The evaluation after 12 weeks found that there was an increase in mileage as measured through the 6MWT submaximal test and a better duration of physical activity in the study group tested through the Endurance Shuttle Walk Test (ESWT). This is consistent with the effect of physical exercise, which suppresses systemic inflammation and causes vasodilation, thereby increasing oxygen delivery to the tissues. This causes more optimal aerobic metabolism and reduces lactate production. So that the patient did not quickly feel tired during activities. However, there was no significant increase in the Incremental Shuttle Walk Test. This could be due to the relatively short training duration of 12 weeks. Conclusion A positive correlation exists between physical exercise and increased functional capacity of patients with CHD who were evaluated using 6MWT and ESWT.